Comparative Analysis of Peer Tutoring and Conventional Strategies in Students’ Performance in Chemistry - Dr. Munwar Bagum,; Muhammad Jawad Tehsain,; Sadia Jamil,; Naveed Ahmad,; Dr. Muhammad Javed Aftab,; Dr. Asma Islam*, (Al-Qanṭara, 2022)
The prime objective of the study, therefore, was to take a comparative analysis of peer tutoring and conventional strategies in students’ performance in subject of chemistry at secondary level. Other study objectives included determining the effect of peer tutoring on students' academic achievement in the subject of chemistry in terms of pre- and post-test scores, as well as comparing the performance of students taught using peer tutoring and traditional instructional strategies in chemistry on a Multiple Type Questions taken on the Board pattern. Furthermore, the research attempted to compare the performance of students taught in chemistry utilizing peer tutoring vs standard instructional methodologies. Seven thousand two hundred twenty male students attending secondary and higher education institutions in Tehsil Muzaffargarh were recruited at random or counted as the population for the purpose of this research. Instead, the study's sample size was 95 students taken from two entire 10th grade classes at Khan Pur Bagga Sher Government High School. The peer tutoring strategy was used in a single classroom with 48 students (the "Experimental group"). The other 44 children in the "control group," on the other hand, were taught using more traditional approaches. A before and after comparison test technique was employed in the acquisition of the information. SPSS was used to analyze the data, and descriptive analysis methods such as the independent t-test and the paired sampling test were utilized for validation. Academic attainment was shown to vary considerably between the experimental group, which was taught using the peer tutoring methodology, and the control group, which was taught using the standard teacher-led method. The experimental group was instructed using the peer tutoring approach. Furthermore, the study's results provide support to the concept that having students learn from their peers may improve their general comprehension of chemistry. Both in terms of the disparity between tutoring groups and the students' academic achievement. To summarize, the results of this research have significant significance for educators, school administrators, and lawmakers interested in enhancing the academic performance of chemistry students.